Ethnic differences in the prevalence of diabetes in underweight and normal weight individuals: The CARRS and NHANES studies. (December 2018) - Gujral, Unjali P.; Mohan, Viswanathan; Pradeepa, Rajendra; Deepa, Mohan; Anjana, Ranjit Mohan; Narayan, K.M.
Highlights: A proportion of individuals may develop type 2 diabetes without overweight/obesity. A large proportion of Asian Indians type 2 diabetes even with a low BMI. This was not explained by differences in waist circumference, HOMA-IR, or HOMA-β. Further studies should examine type 2 diabetes pathophysiology in lean individuals. Abstract: Aims: Type 2 diabetes in lean individuals has recently come to attention. We assessed type 2 diabetes prevalence and the associated risk factors in underweight and normal weight individuals in two ethnic populations. Methods: We conducted cross-sectional analyses, using representative samples of 4930 Asian Indians from the CARRS-Chennai Study and 2868 Whites from the NHANES Survey. Diabetes was defined as use of glucose lowering medication, fasting glucose ≥126 mg/dl, or 2 h glucose ≥200 mg/dl. Body mass index (BMI) was classified using WHO standard criteria. Results: Prevalence of type 2 diabetes by BMI varied by ethnicity and sex. In men, type 2 diabetes prevalence was 5.4% and 23.5% in underweight and normal weight Asian Indians and 0.0% and 6.1% in underweight and normal weight Whites. In women, the prevalence was 5.6% and 13.6% in underweight and normal weight Asian Indians and 2.3% and 2.8% in underweight and normal weight Whites. Adjustment for waist circumference, insulin resistance, and insulin secretion did not explain the increased prevalence in Asian Indians. Conclusions: These findings suggest significant ethnic differences in type 2 diabetes prevalence without overweight or obesity. Future studies should examine the pathophysiology of type 2 diabetes development in lean individuals.